Chemical traits of cerebral amyloid angiopathy in familial British‐, Danish‐, and non‐Alzheimerʼs dementias. Issue 3 (25th September 2022) - Michno, Wojciech; Koutarapu, Srinivas; Camacho, Rafael; Toomey, Christina; Stringer, Katie; Minta, Karolina; Ge, Junyue; Jha, Durga; Fernandez‐Rodriguez, Julia; Brinkmalm, Gunnar; Zetterberg, Henrik; Blennow, Kaj; et al.
Abstract: Familial British dementia (FBD) and familial Danish dementia (FDD) are autosomal dominant forms of dementia caused by mutations in the integral membrane protein 2B ( ITM2B, also known as BRI2 ) gene. Secretase processing of mutant BRI2 leads to secretion and deposition of BRI2‐derived amyloidogenic peptides, ABri and ADan that resemble APP/β‐amyloid (Aβ) pathology, which is characteristic of Alzheimer's disease (AD). Amyloid pathology in FBD/FDD manifests itself predominantly in the microvasculature by ABri/ADan containing cerebral amyloid angiopathy (CAA). While ABri and ADan peptide sequences differ only in a few C‐terminal amino acids, CAA in FDD is characterized by co‐aggregation of ADan with Aβ, while in contrast no Aβ deposition is observed in FBD. The fact that FDD patients display an earlier and more severe disease onset than FBD suggests a potential role of ADan and Aβ co‐aggregation that promotes a more rapid disease progression in FDD compared to FBD. It is therefore critical to delineate the chemical signatures of amyloid aggregation in these two vascular dementias. This in turn will increase the knowledge on the pathophysiology of these diseases and the pathogenic role of heterogenous amyloid peptide interactions and deposition, respectively. Herein, we used matrix‐assisted laser desorption/ionization mass spectrometry imaging (MALDI‐MSI) in combination with hyperspectral, confocal microscopy based on luminescent conjugated oligothiophene probes (LCO) to delineate the structural traits and associated amyloid peptide patterns of single CAA in postmortem brain tissue of patients with FBD, FDD as well as sporadic CAA without AD (CAA+) that show pronounced CAA without parenchymal plaques. The results show that CAA in both FBD and FDD consist of N‐terminally truncated‐ and pyroglutamate‐modified amyloid peptide species (ADan and ABri), but that ADan peptides in FDD are also extensively C‐terminally truncated as compared to ABri in FBD, which contributes to hydrophobicity of ADan species. Further, CAA in FDD showed co‐deposition with Aβ x‐42 and Aβ x‐40 species. CAA+ vessels were structurally more mature than FDD/FBD CAA and contained significant amounts of pyroglutamated Aβ. When compared with FDD, Aβ in CAA+ showed more C‐terminal and less N‐terminally truncations. In FDD, ADan showed spatial co‐localization with Aβ3pE‐40 and Aβ3‐40 but not with Aβx‐42 species. This suggests an increased aggregation propensity of Aβ in FDD that promotes co‐aggregation of both Aβ and ADan. Further, CAA maturity appears to be mainly governed by Aβ content based on the significantly higher 500/580 patterns observed in CAA+ than in FDD and FBD, respectively. Together this is the first study of its kind on comprehensive delineation of Bri2 and APP‐derived amyloid peptides in single vascular plaques in both FDD/FBD and sporadic CAA that provides new insight in non‐AD‐related vascular amyloid pathology. Cover Image for this issue: https://doi.org/10.1111/jnc.15424 Abstract : MALDI mass spectrometry imaging, a novel biochemical imaging technique, was used to elucidate the differential aggregation pattern of amyloid peptide species in vascular deposits in familial British and Danish dementia (FBD/FDD). Cover Image for this issue: https://doi.org/10.1111/jnc.15424